Factors influencing female progression in leadership positions in the Ready-Made Garment (RMG) industry in Bangladesh - Islam, Md Asadul; Jantan, Amer Hamzah; Hashim, Haslinda; Choo, Wei Chong; Abdullah, Mirza Manirajah (Research Publishing Academy, 2018)
The purpose of this study is to examine key influences that create barriers to female employees’ progression in leadership positions in Ready Made Garments (RMG) organisations. The area of enquiry is the ready-made garment producing organizations based on qualitative research. 8 participants from one of the biggest RMG organisations in Saver, Dhaka, Bangladesh were interviewed for the research. Rich qualitative data provided by the participants were used to identify a number of key factors influencing organisational behaviour and culture. The organisational behavioural influences include lack of work-life balance, patriarchal and bureaucratic structure, while cultural influences are gender stereotyping and lack of self-confidence. Further analysis of findings revealed several ways to overcome factors that create barriers for women holding leadership positions including seeking mentors and building self-confidence. The study is specifically valuable for females working in RMG organizations worldwide because it examined an area of gendered leadership, which has received little attention among academic researchers in relation to RMG industry. However, the scope of the study extends to all RMG decision-makers and others who seek to increase the number of females in leadership positions by identifying, employing and promoting the most suitable and talented employees into these positions regardless of gender.